# 3_1 - Chapter 3 284 Functions and Their Graphs 3.1...

This preview shows pages 1–4. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 3 284 Functions and Their Graphs 3.1 Functions 1. (1,3) 2. 3 2 ( 29 2- 5 2 ( 29 + 1 2 = 12- 10 + 1 2 = 5 2 3. We must not allow the denominator to be 0. x + 4 x - 4 ; Domain: x x - 4 { } . 4. 3- 2 x 5 5. independent, dependent- 2 x 2 x &amp;lt; - 1 6. range 7. The intersection of the intervals [0,7] and [2,5], i.e., [0,5]. 8. does not equal, f , g 9. g- f ( 29 x ( 29 10. False 11. True 12. True 13. True 14. False 15. Function Domain: {Dad, Colleen, Kaleigh, Marissa} Range: {Jan. 8, Mar. 15, Sept. 17} 16. Function Domain: {Bob, Dave, John, Chuck} Range: {Beth, Diane, Linda, Marcia} 17. Not a function 18. Function Domain: {Bob, Dave, John, Chuck} Range: {Diane, Linda, Marcia} 19. Not a function 20. Function Domain: {2, 1, 3, 4} Range: {3, 5, 7, 12} 21. Function Domain: {1, 2, 3, 4} Range: {3} 22. Function Domain: {0, 1, 2, 3} Range: {2, 3, 7} Section 3.1 Functions 285 23. Not a function 24. Not a function 25. Function Domain: {2, 1, 0, 1} Range: {4, 1, 0} 26. Function Domain: {2, 1, 0, 1} Range: {3, 4, 16} 27. f x ( 29 = 3 x 2 + 2 x- 4 (a) f ( 29 = 3 0 ( 29 2 + 2 0 ( 29- 4 = - 4 (b) f 1 ( 29 = 3 1 ( 29 2 + 2 1 ( 29- 4 = 3 + 2- 4 = 1 (c) f- 1 ( 29 = 3- 1 ( 29 2 + 2- 1 ( 29- 4 = 3- 2- 4 = - 3 (d) f- x ( 29 = 3- x ( 29 2 + 2- x ( 29- 4 = 3 x 2- 2 x- 4 (e)- f x ( 29 = - 3 x 2 + 2 x- 4 ( 29 = - 3 x 2- 2 x + 4 (f) f x + 1 ( 29 = 3 x + 1 ( 29 2 + 2 x + 1 ( 29- 4 = 3 x 2 + 2 x + 1 ( 29 + 2 x + 2- 4 = 3 x 2 + 6 x + 3 + 2 x + 2- 4 = 3 x 2 + 8 x + 1 (g) f 2 x ( 29 = 3 2 x ( 29 2 + 2 2 x ( 29- 4 = 12 x 2 + 4 x- 4 (h) f x + h ( 29 = 3 x + h ( 29 2 + 2 x + h ( 29- 4 = 3 x 2 + 2 xh + h 2 ( 29 + 2 x + 2 h- 4 = 3 x 2 + 6 xh + 3 h 2 + 2 x + 2 h- 4 28. f x ( 29 = - 2 x 2 + x- 1 (a) f ( 29 = - 2 0 ( 29 2 +- 1 = - 1 (b) f 1 ( 29 = - 2 1 ( 29 2 + 1- 1 = - 2 (c) f- 1 ( 29 = - 2- 1 ( 29 2 +- 1 ( 29- 1 = - 4 (d) f- x ( 29 = - 2- x ( 29 2 +- x ( 29- 1 = - 2 x 2- x- 1 (e)- f x ( 29 = -- 2 x 2 + x- 1 ( 29 = 2 x 2- x + 1 (f) f x + 1 ( 29 = - 2 x + 1 ( 29 2 + x + 1 ( 29- 1 = - 2 x 2 + 2 x + 1 ( 29 + x + 1- 1 = - 2 x 2- 4 x- 2 + x = - 2 x 2- 3 x- 2 (g) f 2 x ( 29 = - 2 2 x ( 29 2 + 2 x ( 29- 1 = - 8 x 2 + 2 x- 1 (h) f x + h ( 29 = - 2( x + h ) 2 + x + h ( 29- 1 = - 2 x 2 + 2 xh + h 2 ( 29 + x + h- 1 = - 2 x 2- 4 xh- 2 h 2 + x + h- 1 Chapter 3 Functions and Their Graphs 286 29. f x ( 29 = x x 2 + 1 (a) f ( 29 = 2 + 1 = 1 = (b) f 1 ( 29 = 1 1 2 + 1 = 1 2 (c) f- 1 ( 29 =- 1- 1 ( 29 2 + 1 =- 1 1 + 1 = - 1 2 (d) f- x ( 29 =- x- x ( 29 2 + 1 =- x x 2 + 1 (e)- f x ( 29 = - x x 2 + 1 =- x x 2 + 1 (f) f x + 1 ( 29 = x + 1 x + 1 ( 29 2 + 1 = x + 1 x 2 + 2 x + 1 + 1 = x + 1 x 2 + 2 x + 2 (g) f 2 x ( 29 = 2 x 2 x ( 29 2 + 1 = 2 x 4 x 2 + 1 (h) f x + h ( 29 = x + h x + h ( 29 2 + 1 = x + h x 2 + 2 xh + h 2 + 1 30. f x ( 29 = x 2- 1 x + 4 (a) f ( 29 = 2- 1 + 4 =- 1 4 = - 1 4 (b) f 1 ( 29 = 1 2- 1 1 + 4 = 5 = (c) f- 1 ( 29 =- 1 ( 29 2- 1- 1 + 4 = 3 = (d) f- x ( 29 =- x ( 29 2- 1- x + 4 = x 2- 1- x + 4 (e)- f x ( 29 = - x 2...
View Full Document

## This homework help was uploaded on 04/07/2008 for the course MAC 1105 taught by Professor Any during the Spring '08 term at FIU.

### Page1 / 16

3_1 - Chapter 3 284 Functions and Their Graphs 3.1...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online